2006
DOI: 10.1149/1.2161580
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Charging of Lithium-Ion Batteries Using Pulsed Currents

Abstract: Lithium-ion batteries are typically charged using constant current that is applied until the cell voltage reaches about 4.2 V, at which time, charging continues at a constant voltage until the full battery capacity is attained. This process is slow, typically requiring 2-4 h. Empirically selected pulse-charging sequences have been shown to provide enhanced charging; however, no model exists to explain and optimize the pulse-charging protocols. Modeling the lithium diffusion into a homogeneous intercalant layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(87 citation statements)
references
References 25 publications
0
73
0
Order By: Relevance
“…For many electrochemical applications such as electroplating and charging of metal batteries, which is equivalent to electrodeposition at the metal negative electrode, it is desirable to operate them as quickly as possible at a high current without causing the formation of dendrites that short-circuit the system. To delay or prevent the formation of dendrites, it is common to perform pulse electroplating of metals [207,208] or pulse charging of lithium metal batteries (LMBs) and lithium-ion batteries (LIBs) [209][210][211][212][213][214][215][216][217] so that there is sufficient time between pulses for the concentration gradients and electric field in the system to relax. For pulse electroplating of metals, it has been empirically observed that the crystal grain size generally decreases with applied current [207,208].…”
Section: F Pulse Electroplating and Pulse Chargingmentioning
confidence: 99%
“…For many electrochemical applications such as electroplating and charging of metal batteries, which is equivalent to electrodeposition at the metal negative electrode, it is desirable to operate them as quickly as possible at a high current without causing the formation of dendrites that short-circuit the system. To delay or prevent the formation of dendrites, it is common to perform pulse electroplating of metals [207,208] or pulse charging of lithium metal batteries (LMBs) and lithium-ion batteries (LIBs) [209][210][211][212][213][214][215][216][217] so that there is sufficient time between pulses for the concentration gradients and electric field in the system to relax. For pulse electroplating of metals, it has been empirically observed that the crystal grain size generally decreases with applied current [207,208].…”
Section: F Pulse Electroplating and Pulse Chargingmentioning
confidence: 99%
“…Fast charging of batteries is a popular research topic is the electrochemical community, however, this problem has received very little attention from the controls community. Popular charging strategies are constantcurrent / constant-voltage (CC/CV), pulse current charging, pulse voltage charging [2], [3], [4], with CC/CV being the most wide-spread method to recharge Li-ion batteries. In [5], [6] some promising charging strategies are presented; however, the maximum performance determined by the electrochemistry of the battery is not approached by those methods.…”
Section: Introductionmentioning
confidence: 99%
“…Time-dependent models for electrochemical cells are widely used in science and technology. In the field of power sources, the charge/discharge cycle of batteries [1][2][3][4][5] and the startup behavior of fuel cells 6 are important topics. Time-dependent models with electrochemical reactions have been used to describe e.g.…”
Section: Introductionmentioning
confidence: 99%